Late Onset Neuropathy with Spontaneous Clinical Remission in Mice Lacking the POZ Domain of the Transcription Factor Myc-interacting Zinc Finger Protein 1 (Miz1) in Schwann Cells - Sanz-Moreno, Adrián (J Biol Chem, 2015)
The transcription factor Miz1 (Myc-interacting zinc finger 1) is a known regulator of the cell cycle but also has cell cycle-independent functions. Here we analyzed the role of Miz1 in the peripheral nervous system, using an early embryonic conditional knock-out model in which the Miz1 POZ domain is ablated in Schwann cells. Although the development of myelinated nerve fibers was not impaired, Miz1ΔPOZ mice acquired behavioral signs of a peripheral neuropathy at the age of 3 months. At this time, ultrastructural analysis of the sciatic nerve showed de- and dysmyelination of fibers, with massive outfoldings and a focal infiltration of macrophages. Although the expression of genes encoding structural myelin proteins, such as periaxin, myelin basic protein, and myelin protein zero, was decreased, genes associated with a negative regulation of myelination, including c-Jun, Sox2, and Id2, were up-regulated in Miz1ΔPOZ mice compared with controls. In animals older than 4 months, the motor disabilities vanished, and the ultrastructure of the sciatic nerve exhibited numerous tomacula and remyelinated fibers, as indicated by thinner myelin. No second acute attack was observed up to the age of 1 year. Thus, the deletion of the Miz1 POZ domain in Schwann cells induces an acute neuropathy with a subsequent regeneration in which there is ongoing balancing between de- and remyelination. Miz1ΔPOZ mice are impaired in the maintenance of myelinated fibers and are a promising model for studying remyelination in adult peripheral nerves.